Molecular surveillance of piroplasms in ticks from small and medium-sized urban and peri-urban mammals in Australia - Siew-May Loh; Siobhon Egan; Amber Gillett; Peter B. Banks; Una M. Ryan; Peter J. Irwin; Charlotte L. Oskam (International Journal for Parasitology: Parasites and Wildlife, 2018)
Natural landscape alterations as a consequence of urbanisation are one of the main drivers in the movements of wildlife into metropolitan and peri-urban areas. Worldwide, these wildlife species are highly adaptable and may be responsible for the transmission of tick-borne pathogens including piroplasms (Babesia, Theileria and Cytauxzoon spp.) that cause piroplasmosis in animals and occasionally in humans. Little is known about piroplasms in the ticks of urban wildlife in Australia. Ticks from long-nosed bandicoots (Perameles nasuta; n = 71), eastern-barred bandicoots (Perameles gunnii; n = 41), northern-brown bandicoots (Isoodon macrourus; n = 19), southern-brown bandicoots (Isoodon obesulus; n = 4), bandicoot sp. (n = 2), flying foxes (Pteropus sp.; n = 3), black rats (Rattus rattus; n = 7), bush rats (Rattus fuscipes; n = 4), brushtail possums (Trichosurus vulpecula; n = 19), ringtail possums (Pseudocheirus peregrinus; n = 12), short-eared possums (Trichosurus caninus; n = 6), possum sp. (Trichosurus sp.; n = 8), and red foxes (Vulpes vulpes; n = 12) were analysed using piroplasm-specific 18S primers and Sanger sequencing. Seven Ixodes tasmani ticks from long-nosed bandicoots and bandicoots sp., three I. tasmani ticks and one Ixodes holocyclus tick from brushtail possums, and one Haemaphysalis longicornis tick from a red fox were positive for piroplasms. New genotypes, with sequences sharing 98% nucleotide similarities with Theileria sp. K1 detected in a burrowing bettong (Bettongia lesueur), were identified from bandicoot ticks. New genotypes were detected in ticks from brushtail possums, which shared 98% similarity with a Babesia sp. (JQ682877) previously identified in marsupials. Theileria orientalis was identified in the H. longicornis tick from the red fox. Babesia and Theileria spp. in the ticks parasitizing bandicoots and brushtail possums clustered closely with respective Babesia and Theileria clades derived from Australian marsupials. This represents the first detection of piroplasms in ticks parasitizing brushtail possums and a red fox in Australia. Keywords: Piroplasm, Bandicoot, Brush-tailed possum, Red fox, Australia